2020
DOI: 10.1108/jiabr-05-2017-0069
|View full text |Cite
|
Sign up to set email alerts
|

The extent of audit report lag and governance mechanisms

Abstract: Purpose The purpose of this study is to examine the extent of audit report lag and its association with governance mechanisms in the Islamic banking institutions in Malaysia. Design/methodology/approach The extent of audit report lag is defined by the number of days from a company’s financial year-end to the signature date on its audit report. The sample of the study comprises 112 observations of Islamic banking institutions’ financial reports for the period 2008-2014. A balanced panel data analysis is perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 34 publications
4
56
1
1
Order By: Relevance
“…In ICb, it was found that the SSB coefficient statistic was -3.82, significant at the 10 percent level. The study of SSB related to timeliness was carried out by Kaaroud et al (2020). The results of this study do not support their investigation, which concluded that SSB had a weak association with timeliness.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In ICb, it was found that the SSB coefficient statistic was -3.82, significant at the 10 percent level. The study of SSB related to timeliness was carried out by Kaaroud et al (2020). The results of this study do not support their investigation, which concluded that SSB had a weak association with timeliness.…”
Section: Discussioncontrasting
confidence: 61%
“…All interested parties, either directly or indirectly, hope to get benefits from bank activities in accordance with Sharia principles. To meet the expectations of these stakeholders, an agency that supervises the operation of the business is needed according to the right mechanism to solve Sharia problems (Kaaroud et al, 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The importance of ARL has encouraged previous researchers to analyse several factors that may affect its extent (Kaaroud, Mohd Ariffin, & Ahmad, 2020). Durand (2019) has reported that out of 126 independent variables used in previous studies as the determinants of ARL, they can be divided into three categories, namely: firm attributes, audit attributes, and corporate governance attributes.…”
Section: Previous Studies On Audit Report Lagmentioning
confidence: 99%
“…Given the possible effects of ARL in the timeliness of issuing annual reports (Wan-Hussin & Bamahros, 2013), a sizeable number of studies have reported on examining the factors leading to audit report delay (Bhuiyan & D'Costa, 2020;Juwita, T, & Hariadi, 2020;Kaaroud et al, 2020). However, limited studies have been done on the importance of ACC attributes, such as accounting expertise and ACC tenure (i.e., Baatwah et al, 2019;Ghafran & Yasmin, 2018;Tanyi & Smith, 2015).…”
Section: Previous Studies On Audit Report Lagmentioning
confidence: 99%
See 1 more Smart Citation